2017
DOI: 10.1161/jaha.117.006522
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants Associated With Uncontrolled Blood Pressure on Thiazide Diuretic/β‐Blocker Combination Therapy in the PEAR (Pharmacogenomic Evaluation of Antihypertensive Responses) and INVEST (International Verapamil‐SR Trandolapril Study) Trials

Abstract: BackgroundThe majority of hypertensive individuals require combination antihypertensive therapy to achieve adequate blood pressure (BP) control. This study aimed to identify genetic variants associated with uncontrolled BP on combination therapy with a thiazide diuretic and a β‐blocker.Methods and ResultsA genome‐wide association study of uncontrolled BP on combination therapy was conducted among 314 white participants of the PEAR (Pharmacogenomic Evaluation of Antihypertensive Responses) trial. Multivariable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…Consistently, these findings were replicated in an independent cohort treated with the thiazide diuretic chlorthalidone, thus validating the associations 42. Also employing a GWAS approach, Magvanjav et al found that the SNP rs261316 in the ALDH1A2 gene was associated with uncontrolled blood pressure following treatment with a thiazide diuretic/β-blocker combination in white participants of the PEAR study 43. These findings were further validated in a replication study including subjects from INVEST study 43.…”
Section: Diureticsmentioning
confidence: 66%
“…Consistently, these findings were replicated in an independent cohort treated with the thiazide diuretic chlorthalidone, thus validating the associations 42. Also employing a GWAS approach, Magvanjav et al found that the SNP rs261316 in the ALDH1A2 gene was associated with uncontrolled blood pressure following treatment with a thiazide diuretic/β-blocker combination in white participants of the PEAR study 43. These findings were further validated in a replication study including subjects from INVEST study 43.…”
Section: Diureticsmentioning
confidence: 66%
“…According to a recent review by Thies et al, there are not enough studies to draw substantial conclusions on the effects of lycopene on blood pressure [ 39 ]. Interestingly, the strong genetic correlation suggesting shared genetic factors affecting both lycopene concentrations and DBP may be plausible since SETD7 has been associated with both traits [ 15 , 61 ]. Indeed, a genetic variant (rs7680948) within SETD7 , encoding for SET domain containing lysine methyltransferase 7, was associated with serum lycopene concentrations in Amish adults [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a genetic variant (rs7680948) within SETD7 , encoding for SET domain containing lysine methyltransferase 7, was associated with serum lycopene concentrations in Amish adults [ 15 ]. SETD7 was also associated with DBP response and may play a role in high glucose-induced vascular dysfunction [ 61 , 62 ]. Genetic variants and changes in expression of genes involved in lycopene absorption and metabolism may also impact CM risk factors including blood pressure but this area still needs to be further studied [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that two other family members of the ADH gene ( ALDH1A2 and ALDH7 ) are related to the presence of hypertension in African Americans, while ALDH2 was associated with BP control in an East Asian population [ 7 , 99 , 100 ]. A GWAS analysis found a relationship between the SNP rs261316 in the ALDH1A2 gene and uncontrolled blood pressure following treatment with a thiazide diuretic/β-blocker combination in white participants of the PEAR study [ 101 ]. The results of the INVEST study confirmed the aforementioned findings [ 101 ].…”
Section: Diureticsmentioning
confidence: 99%
“…A GWAS analysis found a relationship between the SNP rs261316 in the ALDH1A2 gene and uncontrolled blood pressure following treatment with a thiazide diuretic/β-blocker combination in white participants of the PEAR study [ 101 ]. The results of the INVEST study confirmed the aforementioned findings [ 101 ]. Other GWAS studies identified various additional loci associated with BP responses to HCTZ in different ethnic groups [ 16 , 102 , 103 ].…”
Section: Diureticsmentioning
confidence: 99%